(untitled) (Research, Society and Development, 2021)
Among the factors that influence bean productivity, precipitation and nutrition are considered limiting factors. The study aim was to evaluate the irrigation management, Nitrogen fertilization and seed inoculation, in dry bean, in Aquidauana-MS. The work was carried out in the experimental area of the State University of Mato Grosso do Sul, Aquidauana campus, using the cultivar TAA Dama sowed on May 24th, 2018. The experimental design was in randomized blocks, in a split-plot scheme, with four replications. The plots were the Penman-Monteith model irrigation and tensiometry managements. The subplots were with and without Rhizobium tropici semia 4077 inoculation and, in the sub-subplots, topdressing Nitrogen doses (50, 100, 150 and 200 kg ha-1 and one without Nitrogen) were used. The number and dry matter of nodules were evaluated, pods number per plant, average mass of 100 grains, grains number per pod, grain yield, water use efficiency. Higher Nitrogen doses topdressing provide higher grain yields and water use efficiency by the dry bean. The inoculation presence or absence doesn’t influence the grain irrigated bean yield.